Individually moulded silicone dressing in full thickness skin grafts - Michael Götting; Rahel Zibell; Markus Jungehülsing (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Full thickness skin grafting is a common technique for reconstructing defects in the head and neck area. We propose the use of an addition-cured silicone as an individually moulded silicone dressing to keep the vulnerable skin graft in place, prevent shearing forces and create a moist environment. Method The silicone dressing is applied directly on the graft, using a double cartridge system. The silicone is moulded to the skin graft and hardens quickly, integrating thread knots into its material and creating good adherence to the graft. Charts of 24 patients who had undergone reconstruction with full thickness skin graft from the neck after surgery for skin tumors in the head from November 2017 to October 2020, were reviewed retrospectively to quantify the degree of post-operative graft loss and durability of the dressing. Conclusion Medical silicone based on venylpolysiloxane is a safe and durable dressing which makes postoperative dressing changes expendable. Trial registration The study was approved by the institutional review board of the Brandenburg state medical association (S 4(bB)/2021). Graphical Abstract